Evaluasi Mata Rantai Komunikasi Dalam Bisnis Fullfillment(HAISTAR) Pada Glico Di Marketplace Tokopedia - Kevin Adhiasta Santoso (2022)
Auto-canceling order have became a frequent occurrance for online businesses in the Tokopedia marketplace. Business is an acivity carried out by many people who sepcialize in one field and alsohave income. In business communication, you can add sales of a product in order to adjust it to market segmentation. Haistar itself is a startup company whose goal is to make it easier to do business online when marketing its products and also Haistar provides a WMS (Warehouse Management System). The online media shop or marketplace that is usually used by the Indonesian people is Tokopedia. Tokopedia itself can be a communication medium to promote a product or service to the wider community. The purpose of this study is to find out the communication flow in the fulfillment business on Glico in the Tokopedia marketplace and what obstacles are experienced by Glico that can hinder its business. This study uses a qualitative method with a phenomenological approach and a constructive paradigm. The research data was carried out by interviewing three sources, key informant as Account Manager (AM) and two supporting informant as store-ops admins and PIC Glico. Researcher asked a question how the flow of communication and also how to overcome existing obstacles. The results of the research obtained are the basis of business communication from top to bottom, from bottom to top, communication horizontally and communication diagonally. The obstacle experienced by Haistar was the delay in communication between Haistar and Glico which resulted in negligence in sales on Tokopedia marketplace. The conclusion obtained is that Haistar must communicate on a scheduled basis with Glico so that there is no lack of information between the two parties